2016
DOI: 10.2134/jeq2016.02.0073
|View full text |Cite
|
Sign up to set email alerts
|

Co‐transport of Pesticide Acetamiprid and Silica Nanoparticles in Biochar‐Amended Sand Porous Media

Abstract: The role of biochar as a soil amendment on the transport of acetamiprid, a widely used neonicotinoid pesticide, is little known. We conducted saturated column experiments to examine cotransport of acetamiprid and silica nanoparticles (NPs) in pure and biochar-amended sands. Retention of acetamiprid was minor in the pure sand, whereas application of biochar in the sand significantly increased retention. Retention was greater at lower ionic strengths and near neutral pH values and was attributed to biodegradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…The zeta potentials were less negative in CaCl 2 than in NaCl at a given IS due to specific adsorption of calcium ions to the clay particle surfaces (Chen and Elimelech, 2006). It should be noted that the measured zeta potentials are mean values, which cannot reflect surface chemical heterogeneities (e.g., functional groups on the biochar surfaces) (Li et al, 2017; Wang et al, 2016b). In addition to the chemical heterogeneity, the sand and biochar surfaces bear physical heterogeneities (i.e., surface roughness) (see the scanning electron microscopy images in Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The zeta potentials were less negative in CaCl 2 than in NaCl at a given IS due to specific adsorption of calcium ions to the clay particle surfaces (Chen and Elimelech, 2006). It should be noted that the measured zeta potentials are mean values, which cannot reflect surface chemical heterogeneities (e.g., functional groups on the biochar surfaces) (Li et al, 2017; Wang et al, 2016b). In addition to the chemical heterogeneity, the sand and biochar surfaces bear physical heterogeneities (i.e., surface roughness) (see the scanning electron microscopy images in Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…If the clay colloids were initially attached in CaCl 2 , only a small fraction of the colloids were released by introducing DI water. The irreversibility of clay colloid deposition on biochar surfaces is likely due to formation of cation bridging between the clay colloids and the functional groups on the biochar surfaces (Wang et al, 2016b). Shen et al (2013) showed that the cation bridging eliminates the short‐range repulsion between the colloids and the collector surfaces, and the colloids cannot be released by reducing IS even if they are attached atop of nanoscale protruding asperities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations